A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria-group - Świętojańska, Jolanta; Borowiec, Lech (Zootaxa, 2016)
Notosacantha timorensis sp. nov. belonging to the Notosacantha vicaria-group is described from Timor-Leste. Colour photos of N. sumbawaensis Świętojańska & Borowiec, 1999 and a key to the Notosacantha vicaria-group are given.